Conservative Management of Early Grade Unilateral Reinke's Edema with Laryngopharyngeal Reflux - Rahardjo, Sutji Pratiwi (Fakultas Kedokteran Universitas Brawijaya, 2024)
Reinke's edema is described as fluid-filled vocal folds in the Reinke's space. Unilateral cases are uncommon and might caused by gastrointestinal reflux. We report a 61-year-old man with complaints of hoarseness since one year ago, which was getting worse for the past two months. Examination of the reflux symptom index (RSI) obtained a score of 23 and reflux finding score (RFS) score of 11. Examination of the flexible fiber laryngoscopy showed that the right vocal fold size was thicker than the contralateral side, greyish in color, soft, and did not bleed easily. The patient was then given conservative therapy with proton pump inhibitors (PPIs), corticosteroids, and mucolytics, accompanied by lifestyle modifications. Clinical improvement was found at four weeks of evaluation. In conclusion, the response to conservative therapy and elimination of risk factors for early-stage Reinke's edema contributes well to disease recovery, particularly those caused by laryngopharyngeal reflux.